2005
DOI: 10.1098/rsif.2005.0086
|View full text |Cite
|
Sign up to set email alerts
|

Rheopexy of synovial fluid and protein aggregation

Abstract: Bovine synovial fluid and albumin solutions of similar concentration are rheopectic (stress increases with time in steady shear). This unusual flow characteristic is caused by protein aggregation, and the total stress is enhanced by entanglement of this tenuous protein network with the long-chain polysaccharide sodium hyaluronate under physiological conditions. Neutron scattering measurements on albumin solutions demonstrate protein aggregation and all measurements are consistent with a weak dipolar attraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
140
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(150 citation statements)
references
References 89 publications
7
140
0
Order By: Relevance
“…These facts suggest the synergistic effect of -globulin and HA, but indicate the adverse interaction of albumin and HA for intact cartilage. It is reported that albumin and HA show repulsive interaction [36] and the HA-protein complexes in natural synovial fluid contain globulin but almost no albumin at pH 7-8 [37]. These frictional trends for both proteins are similar for damaged cartilage with partially removed surface proteoglycan gel layer.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…These facts suggest the synergistic effect of -globulin and HA, but indicate the adverse interaction of albumin and HA for intact cartilage. It is reported that albumin and HA show repulsive interaction [36] and the HA-protein complexes in natural synovial fluid contain globulin but almost no albumin at pH 7-8 [37]. These frictional trends for both proteins are similar for damaged cartilage with partially removed surface proteoglycan gel layer.…”
Section: Discussionmentioning
confidence: 48%
“…The lubricant No.13 has similar composition to that in natural synovial fluid as hyaluronate solution containing lubricating constituents such as 1.25 wt% albumin, 0.75 wt% globulin (including --, and -globulins) as medium values [42], 1.1 wt% albumin and 0.7 wt% globulin [36], or 1.9 wt% albumin, 1.1 wt% globulin and 0.01 wt% DPPC [12]. In this lubricant, the lubricating layered structure in adsorbed film is expected for low friction and minimal wear, but the detailed elucidation of this mechanism is required in the future study.…”
Section: Discussionmentioning
confidence: 99%
“…But the actual use and processing of food products, physiological fluids like blood 62 , saliva 23 , synovial fluid and their synthetic replacements 19 , cosmetics 47,63 , etc. requires an understanding of both their bulk and interfacial viscoelasticity.…”
Section: Discussionmentioning
confidence: 99%
“…When the rheological properties of globular protein solutions such as BSA are tested in a torsional rheometer, they exhibit yield-like behaviour at surprisingly low concentrations (0.03%-10%) [15][16][17][18][19][20] , and show pronounced shear thinning at low shear rates. This has been attributed in past studies [15][16][17] to the presence of long ranging colloidal forces that are stronger than electrostatic interactions, and which lead to an ordered bulk colloidal structure formation.…”
Section: Introductionmentioning
confidence: 99%
“…This fluid is a complex mixture of macromolecules with a large concentration of plasma proteins which demonstrates non-Newtonian behaviour [4,5]. The properties of the fluid, including pH and protein content vary from patient to patient, and between healthy and diseased states [6,7].…”
Section: Introductionmentioning
confidence: 99%